Clinical and social outcomes of adolescent self harm: population based birth cohort study. (21st October 2014) - Mars, Becky; Heron, Jon; Crane, Catherine; Hawton, Keith; Lewis, Glyn; Macleod, John; Tilling, Kate; Gunnell, David
Abstract : Objectives To investigate the mental health, substance use, educational, and occupational outcomes of adolescents who self harm in a general population sample, and to examine whether these outcomes differ according to self reported suicidal intent. Design Population based birth cohort study. Setting Avon Longitudinal Study of Parents and Children (ALSPAC), a UK birth cohort of children born in 1991-92. Participants Data on lifetime history of self harm with and without suicidal intent were available for 4799 respondents who completed a detailed self harm questionnaire at age 16 years. Multiple imputation was used to account for missing data. Main outcome measures Mental health problems (depression and anxiety disorder), assessed using the clinical interview schedule-revised at age 18 years, self reported substance use (alcohol, cannabis, cigarette smoking, and illicit drugs) at age 18 years, educational attainment at age 16 and 19 years, occupational outcomes at age 19 years, and self harm at age 21 years. Results Participants who self harmed with and without suicidal intent at age 16 years were at increased risk of developing mental health problems, future self harm, and problem substance misuse, with stronger associations for suicidal self harm than for non-suicidal self harm. For example, in models adjusted for confounders the odds ratio for depression at age 18 years was 2.21 (95% confidence interval 1.55 to 3.15) in participants who had self harmed without suicidal intent at age 16 years and 3.94 (2.67 to 5.83) in those who had self harmed with suicidal intent. Suicidal self harm, but not self harm without suicidal intent, was also associated with poorer educational and employment outcomes. Conclusions Adolescents who self harm seem to be vulnerable to a range of adverse outcomes in early adulthood. Risks were generally stronger in those who had self harmed with suicidal intent, but outcomes were also poor among those who had self harmed without suicidal intent. These findings emphasise the need for early identification and treatment of adolescents who self harm.